Whole-beam self-focusing in fusion-relevant plasma - Spiers, BT; Hill, M; Brown, C; Ceurvorst, L; Ratan, N; Savin, A; Allan, P; Floyd, E; Fyrth, J; Hobbs, L; James, S; Luis, J; et al. (Royal Society, 2020)
Fast ignition inertial confinement fusion requires the production of a low-density channel in plasma with density scale-lengths of several hundred microns. The channel assists in the propagation of an ultra-intense laser pulse used to generate fast electrons which form a hot spot on the side of pre-compressed fusion fuel. We present a systematic characterisation of an expanding laser-produced plasma using optical interferometry, benchmarked against three-dimensional hydrodynamic simulations. Magnetic fields associated with channel formation are probed using proton radiography, and compared to magnetic field structures generated in fullscale particle-in-cell simulations. We present observations of long lived, straight channels produced by the Habara-Kodama-Tanaka (HKT) wholebeam self-focusing mechanism, overcoming a critical barrier on the path to realising fast ignition.